Morphological cladistic analysis of Ophiurolepis Matsumoto, 1915 (Ophiurida: Ophiuridae) from the Southern Ocean - Hunter, Rebecca L. (Zootaxa, 2007)
A phylogenetic analysis using morphological characters was done on the Antarctic ophiuroid genus Ophiurolepis Matsumoto, 1915. This genus is one of the more abundant and ecologically dominant ophiuroid genera in the Antarctic and surrounding Southern Ocean. Maximum parsimony was used to infer phylogenetic relationships. Although strongly supported nodes were not recovered for most groupings within Ophiurolepis, this first attempt at a phylogeny revealed the presence of three tentative clades. Two of the three Ophiurolepis clades included species currently assigned to other genera, but closely allied with Ophiurolepis in the taxonomic literature. This indicates that Ophiurolepis as currently defined is not a monophyletic group. Additional forms of data, namely molecular, are needed to more definitively resolve relationships within this group.